CRIMINAL PROTECTION OF TRADEMARKS RELATED TO THE OLYMPIC GAMES - Daśko, Natalia (Ekonomia i Prawo. Economics and Law, 2014)
Intellectual property rights, especially trademarks, played an important role in organization and promotion of the Olympic Games and commercial exploitation of sport. In fact, without granting intellectual property rights related to the Olympic Games there would be nothing to be exploited and nothing to commercialize as well as no income would be generated. If there were no financial returns the sport events would not look like this these days. As still growing part of economic value of sport is connected with intellectual property rights the protection of symbols and names related to the Olympic movement has become an important issue as it is essential for the proper functioning of the Olympic movement and efficient conducting of the next Olympic Games. One of the research issues is an attempt to answer the question if it was right to place by the Polish legislator the petty offence consisting in the unlawful use of the Olympic symbols in the act on sport, or if it should be placed in the Petty Offence Code or should only be protected within the regulation of the act on Industrial Property Right, acts on Suppression Unfair Competition or the act on Copyrights and Related rights. In Author’s opinion placing the discussed type of offence in the act on sport was the right solution. It seems so, due to the fact that the character of this offence corresponds to the specificity of the matter regulated by this act. Thus the criminal regulations of the act on sport form a consistent whole and they comprehensively regulate the given matter. Critical remarks can be made in relation to the quality of the discussed regulation. In the first place, a change in features of the infraction in question made as part of regulations of the act on sport, consisting of adding the phrase “for commercial purposes” should be assessed critically. In this scope de lege ferenda one should be in favour of coming back to the previous legal state, which did not differentiate the unlawful use of the Olympic symbols in respect of the purpose or form. In the article the following research methods were used: comparative method, the method of systemic analysis and the historical method. The research was based on prescriptive acts, comments and the Polish and foreign literature.